An integrated modelling approach to postharvest control of Aspergillus flavus growth and aflatoxin production in paddy grains and rice - Mousa, Wael (2012)
The main aim of the present study was to develop an integrated postharvest strategy for controlling the growth of and aflatoxin production by Aspergillus flavus on paddy and rice. Initially, equilibrium moisture content of paddy was studied at 20, 30, 40 and 50°C at relative humidity (RH) between 0.113 and 0.976 using gravimetric technique. The isotherms displayed the general sigmoidal curve Type II and exhibited hysteresis where it was more pronounced at lower temperatures. At fixed RH, the sorption characteristics were temperature-dependent where the sorption capacity of the paddy increased as the temperature was decreased. Among the models assessed for their ability to fit the sorption data, the Oswin equation was the best followed by the third order polynomial, GAB, Smith, Chung-Pfost, and Henderson models. Therefore, the Oswin model was chosen to estimate the amount of water required to rehydrate dried paddy to the desired water activity (aw) in subsequent studies. Thereafter, the growth of two aflatoxigenic A. flavus on paddy and aflatoxin production were studied following a full factorial design with seven aw levels between 0.82 and 0.99 and seven temperatures between 10 and 43°C. The growth of the fungi, expressed as colony diameter (mm), was measured daily and aflatoxin production was analyzed using isocratic HPLC with a fluorescence detector. The maximum colony growth rates of both isolates were estimated by fitting the primary model of Baranyi to growth data. Three potentially suitable secondary models; Rosso, polynomial, and Davey, were assessed for their ability to describe the radial growth rate as a function of temperature and aw. Both strains failed to grow at the marginal temperatures (10 and 43°C) regardless of the aw studied, and at the aw level of 0.82, regardless of the temperature. Despite that the predictions of all studied models showed good agreement with the observed growth rates, the Davey model proved to be the best predictor of the experimental data. Aflatoxins were detected at aw between 0.86-0.99 with an optimal aw of 0.98 and the optimal temperature was in the range of 25-30°C. Then, the effect of aw (0.82-0.92) and temperature (15-42°C) on the growth and aflatoxin production by A. flavus on polished and brown rice was also studied. Four secondary models were used to implicit the combined effects of aw and temperature on the growth rates. All models were validated using independent experimental data. According to the assessment indices, the performance of the Davey model in describing the experimental data was the highest, followed in decreasing order by the polynomial, Gaussian and Rosso models. The estimated optimal growth temperature was between 30-34°C. Neither growth nor aflatoxins were detected at aw 0.82 on polished rice while growth and aflatoxins were detected at this aw between 25-35°C on brown rice. The highest amounts of aflatoxins were formed at the higher aw values (0.90-0.92) and a temperature of 20°C after 21 days of incubation for both types of rice where the consistency of aflatoxin production within a wider range of aw values occurred between 25-30°C. The results also showed that brown rice tended to support higher A. flavus growth and aflatoxin production than the polished rice. Logistic models describing the growth and aflatoxin production boundaries of A. flavus were also developed. Experiments were conducted at aw between 0.80 and 0.99 and temperature between 10 °C and 45°C on rice meal agar (RA) for duration of four weeks. The degree of agreement between the predicted and observed data in terms of concordance was > 97% and > 98% for growth and aflatoxin production, respectively. Probabilities of growth and aflatoxin production at 21 days were almost equal to those at 28 days. The polynomial logistic models that were developed were validated with data obtained from repeated experiments on paddy. The models were successfully able to predict the probabilities with concordance rates of 85.2% and 88.9% for growth and aflatoxin production, espectively, whereas all the misidentified cases were found to be false positive. Then, the potential of modified atmosphere packaging with 20-80% CO2 (balanced with nitrogen) in controlling the growth and aflatoxin production on paddy at different aw (0.92-0.98) relative to the control (0% CO2) was examined using the two above-mentioned fungal isolates. Except at 0.92 aw, as much as 80% CO2 failed to inhibit the growth of the fungi completely. However, at all aw levels studied, the growth parameters as estimated by Baranyi function and aflatoxin production were affected by the increment in CO2 where growth rate and aflatoxin production were negatively correlated with CO2 while the lag phase correlated positively with CO2. At 0.98 aw, atmosphere enriched with 20% and 80% CO2 led to at least 59% and 88% reduction in growth and 47% and 97% in aflatoxin production , respectively. At 0.95 aw, the lag phases of both isolates on average increased by a factor of 1.7-12.0 when the CO2 levels in the headspace were between 20-80% compared to the control. Finally, the effectiveness of three essential oils (cinnamon, glove and thyme) and three antioxidants [butylated hydroxyanisole (BHA), propyl paraben (PP) and butylated hydroxytoluene (BHT)] on controlling the growth of and aflatoxin formation by the A. flavus grown on rice meal agar and paddy grains at different aw (0.92, 0.95, and 0.98) were evaluated. Two of the antioxidants (BHA and PP) and the three essential oils displayed significant inhibitory effect on the growth and aflatoxin formation on in vitro and on the paddy grains. Regardless of aw of the paddy, the application of essential oils at 500 μg g-1 reduced the growth and aflatoxin formation by > 55% and >80%,compared with >75% and > 82% with usage of antioxidants (BHA, PP),respectively. The estimated effective doses 50% (ED50) required to reduce growth and aflatoxin formation on rice meal agar were lower than their counterpart on paddy and those required to inhibit aflatoxin formation were lower those of growth.